Peran Ketua Karang Taruna dalam Meningkatkan Motivasi Anggota Karang Taruna di Kelurahan Medokan Ayu Kecamatan Rungkut Surabaya - Fadzilla, Mohamad Afrizal; Siswanto, Heru (J+PLUS UNESA, 2023)
This research was motivated by the low motivation to join youth organizations in Medokan Ayu Village. Karang Taruna members who need motivation in the Karang Taruna organization. The goal to be achieved in this study is to apply the application of motivation in increasing the participation of youth youth members in Medokan Ayu Youth Organization. This study uses a qualitative approach and descriptive research type. Data collection techniques used are in-depth interview techniques, participant observation, and documentation. The results of this study are to increase the motivation of youth youth members. There is one motive that cannot increase motivation, namely theological motives which cannot change the motivation of youth youth members in organizing.